Towards a more integrated and gender-sensitive care delivery for victims of sexual assault: key findings and recommendations from the Belgian sexual assault care centre feasibility study - Bavo Hendriks; Anke Marie-Josée Aimé Vandenberghe; Laura Peeters; Kristien Roelens; Ines Keygnaert (BMC, 2018)
Abstract Background Sexual assault remains a major threat to public health, affecting every gender, gender identity and sexual orientation. Following the Belgian ratification of the Istanbul Convention in 2016, the feasibility of a Belgian sexual assault centre model was investigated, aiming to provide more integrated and patient-centred health and judiciary services to victims of sexual assault. By actively involving health professionals, police and judiciary system representatives, as well as victims themselves, this feasibility study eventually fed into the Belgian Sexual Assault Care Centre model. In this process, this paper assessed current Belgian health services and the degree to which the implementation of this model could contribute to both a more integrated and gender-sensitive care delivery. Findings from this study and the subsequent recommendations aim to contribute to similar reforms in other countries that have already taken or are about to take steps towards an integrated, multi-agency support framework for victims of sexual assault. Methods A qualitative, descriptive analysis of the survey response of 60 key health professionals (N = 60) representing 15 major Belgian hospitals was first conducted. Comparing their approach with the international guidelines and standards, a Strengths Weaknesses Opportunities and Threats analysis of the current sexual assault health services and their potential transition to the Sexual Assault Care Centre model was then executed. Results Despite adequate equipment, the clear fragmentation of health services and limited follow-up hamper an integrated care delivery in most hospitals. Only three hospitals differentiated their sexual assault care protocol based on the victim's gender, gender identity and sexual orientation. A striking unawareness among health professionals of sexual assault in male victims, as well as in gender and sexual minorities further hampers a gender-sensitive care delivery. Conclusions The Sexual Assault Care Centre model aims to counter most of the current sexual assault health services' weaknesses and threats hampering an integrated care for victims of sexual assault. Further research and training of health professionals are however required in order to tune this integrated form of care to sexuality and gender-based differences in victims' already multi-faceted healthcare needs.